Modulation of Cytochrome P450 Activity by 18β‐Glycyrrhetic Acid and its Consequence on Buspirone Pharmacokinetics in Rats. (23rd May 2015) - Kim, Sang‐Bum; Cho, Hyun‐Jong; Kim, Yeong Shik; Kim, Dae‐Duk; Yoon, In‐Soo
<x xml:space="preserve">Abstract</x> The aim of this study was to elucidate the inhibition mechanism of 18β‐glycyrrhetic acid (GLY) on cytochrome P450 (CYP) activity and in vivo pharmacokinetic consequences of single GLY dose in rats. An in vitro CYP inhibition study in rat liver microsomes (RLM) was conducted using probe substrates for CYPs. Then, an in vivo pharmacokinetics of intravenous and oral buspirone (BUS), a probe substrate for CYP3A, was studied with the concurrent administration of oral GLY in rats. In the in vitro CYP inhibition study, CYP3A was involved in the metabolism of GLY. Moreover, GLY inhibited CYP3A activity with an IC50 of 20.1 ± 10.7 μM via a mixed inhibition mechanism. In the in vivo rat pharmacokinetic study, single oral GLY dose enhanced the area under plasma concentration–time curve (AUC) of intravenous and oral BUS, but the extent of increase in AUC was only minimal (1.12–1.45 fold). These results indicate that GLY can inhibit the in vitro CYP3A‐mediated drug metabolism in RLM via a mixed inhibition mechanism. However, the impact of single oral GLY dose on the pharmacokinetics of BUS in rats was limited, showing that GLY could function as merely a weak inhibitor for CYP3A‐mediated drug metabolism in vivo. Copyright © 2015 John Wiley & Sons, Ltd.